Sustainable Tourism Study on Beejay Bakau Resort Probolinggo: An Analysis of RAPFISH-MDS - Rita Parmawati; Rizha Hardyansah (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
BJBR is a famous mangrove tourism object in Probolinggo, it elevates the role of surrounding society and resources. However, it is needed to understand BJBR sustainability aspects and innovations needed to achieve sustainable tourism. This study aims to understand BJBR sustainability through 3 dimensions: ecology, social, and economic-based on RAPFISH-MDS analysis. Interviews and questionnaires were distributed to 47 respondents based on the PRA Approach and Snowball Sampling. The results show that the ecological dimension has the highest sustainability index is 78.81 (good/sustainable), followed by the economic dimension is 64.45 (quite sustainable), and the social dimension is 50.27 (quite sustainable). Sensitive attribute as a supportive indicator of sustainability in ecological dimension is the diversity of tree species outside the mangrove area to be a very (Leverage= 4.41), the economic dimension is a production of cultivated species on mangroves area (Leverage= 7.79), and social dimension is the practice of local culture within mangroves area (Leverage= 7.79). Strategies that can be applied to achieve BJBR tourism sustainability are to continue to carry out conservation that is packaged in responsible tourism, increasing economic growth by encouraging entrepreneurship, and forming networks between tourist sites and the surrounding area to encourage development.